Perakitan Part Bodi Mobil Plant 1 PT TMM menggunakan Sistem Karakuri dalam Mengurangi Pemborosan Gerak Pemindahan Part Upper Arm SUV - Sapardyanto, Yui Hastoro; Putra, Fikriansyah; Biardian, Lutfy Eka; Praditya Alambara; Wibowo, Fikri Fadilah (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
This research was conducted to address the issue of motion waste in the process of transferring the Upper Arm SUV part during vehicle assembly at PT TMM. Based on field observations, it was found that the process cycle time, with a standard of 150 seconds, was not achieved and required an average of 241 seconds. Process analysis revealed that the transfer of the Upper Arm SUV part involved additional manual movements, such as pushing the dolly containing the Upper Arm part to the assembly position and manually handling empty part boxes. This prolonged the process time and reduced operational efficiency. To resolve this issue, this study implemented a Karakuri system that utilizes gravity for transferring Upper Arm SUV part boxes to the rack. The results demonstrated that the implementation of the Karakuri system significantly reduced unnecessary movements, improved operational effectiveness, and shortened the part transfer process time. Consequently, the standard cycle time for part transfer was achieved less tha 150 seconds. Keywords: Karakuri, Line Front Axle, Muda Gerak, Transfer Upper Arm SUV